2023
DOI: 10.29333/ejeph/12604
|View full text |Cite
|
Sign up to set email alerts
|

Changes in individuals’ eating habits and mood, sleep quality, and lifestyle during COVID-19

Abstract: <b>Objectives: </b>The COVID-19 outbreak was classified as a global epidemic after it emerged in the first quarter of 2020 and the virus spread rapidly after only three months. The quarantines implemented during the COVID-19 period, the deterioration of economic income, and the uncertain situation about the future have affected the changes in physical inactivity, mood changes, sleep quality, lifestyle, and eating habits. Our study aimed to investigate the changes in individuals’ mood, sleep quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Therefore, we calculated an adjusted risk relative ratio (RRR), adjusting by per-capita income and using the low family functioning category as reference. Consistent with the literature 20 , we carried out this analysis using the decreased intake category for non-processed foods and the increased intake category for processed foods. A value of p<0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we calculated an adjusted risk relative ratio (RRR), adjusting by per-capita income and using the low family functioning category as reference. Consistent with the literature 20 , we carried out this analysis using the decreased intake category for non-processed foods and the increased intake category for processed foods. A value of p<0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived risk and severity, emotional, sleep, and lifestyle problems are common mental responses and behavioral problems [ 35 ]. (1) Perceived risk was measured by a question “Do you always feel that you may be infected?…”
Section: Methodsmentioning
confidence: 99%
“…Many studies found that the potential to contract a highly lethal disease, such as COVID-19, can overwhelm people emotionally and physically, and induce strong mental and behavioral responses [ 4 , 5 , 7 , 33 , 34 ]. Sleep, emotional, and lifestyle problems are common manifestation of mental and behavioral problems [ 35 ]. This study will examine changing trends of sleep, emotion, and lifestyle from the COVID-19 epidemic to sporadic infection, and there impact on uncertainty stress.…”
Section: Introductionmentioning
confidence: 99%